2007
DOI: 10.2135/cropsci2006-0002tpg
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transcript Profiles in Wild‐Type and o2 Maize Endosperm in Different Genetic Backgrounds

Abstract: Mutations in the Opaque2 (O2) gene of maize (Zea mays L.) improve the nutritional value of maize by reducing the level of zeins in the kernel. The phenotype of o2 grain is controlled by many modifier genes and is therefore strongly dependent on genetic background. We propose two hypotheses to explain differences in phenotypic severity in different genetic backgrounds: (i) Specific genes are differentially (o2 vs. wild‐type) expressed only in certain genotypes, and (ii) A set of genes are differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…These experiments showed that the lysine content of most of the o2 NILs in this study increased significantly, compared with that of their respective recurrent parents, indicating that the inbred lines CA335 and CA339 were effective donors of the o2 allele coding for a defective OPAQUE2 polypeptide. The present study demonstrated that lysine content varies greatly in different o2 NILs and proved that the phenotypic effects of the o2 mutant are dependent upon genetic backgrounds; these data agreed with previous studies demonstrating that o2 phenotypes were background-dependent (Moro et al 1996;Jia et al 2007). All previous studies showed that increased lysine content could be attributed to o2 mutant alleles and that lysine content varied according to genetic background (Moro et al 1996;Jia et al 2007).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These experiments showed that the lysine content of most of the o2 NILs in this study increased significantly, compared with that of their respective recurrent parents, indicating that the inbred lines CA335 and CA339 were effective donors of the o2 allele coding for a defective OPAQUE2 polypeptide. The present study demonstrated that lysine content varies greatly in different o2 NILs and proved that the phenotypic effects of the o2 mutant are dependent upon genetic backgrounds; these data agreed with previous studies demonstrating that o2 phenotypes were background-dependent (Moro et al 1996;Jia et al 2007). All previous studies showed that increased lysine content could be attributed to o2 mutant alleles and that lysine content varied according to genetic background (Moro et al 1996;Jia et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…The present study demonstrated that lysine content varies greatly in different o2 NILs and proved that the phenotypic effects of the o2 mutant are dependent upon genetic backgrounds; these data agreed with previous studies demonstrating that o2 phenotypes were background-dependent (Moro et al 1996;Jia et al 2007). All previous studies showed that increased lysine content could be attributed to o2 mutant alleles and that lysine content varied according to genetic background (Moro et al 1996;Jia et al 2007). However, the present results showed that lysine content did not increase in some maize NILs carrying an o2 allele and that there was no significant difference in kernel characters between some recurrent parents (Dan598 and Liao2345) and their respective o2 NILs (Dan598o2 and Liao2345o2).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…LKR/SDH, which encodes a bifunctional enzyme involved in Lys catabolism (Kemper et al, 1999), is also regulated by O2. Gene expression profiling analysis of o2 mutants revealed that O2 regulates transcription of many genes involved in a variety of pathways (Frizzi et al, 2010;Hartings et al, 2011;Hunter et al, 2002;Jia et al, 2007;Jia et al, 2013), which is consistent with the described pleiotropic effects of the mutant.…”
Section: Introductionsupporting
confidence: 77%
“…To provide a more detailed understanding of O2-regulated gene expression, profiling studies based on microarray analysis were performed that revealed multiple DEGs in o2 endosperm (Hunter et al, 2002;Jia et al, 2007;Frizzi et al, 2010;Hartings et al, 2011;Jia et al, 2013). These studies showed that, along with 22-kD a-zeins and the 14-kD b-zein, a number of other zein genes, e.g., 19-kD a-zeins and the 10-kD d-zein, also showed decreased transcription.…”
Section: Discussionmentioning
confidence: 99%